Analysis of the Particle Characteristics of Aeolian Sand in Yulin Area, China - Qinglong You; Zhang Yang; Jinglian Ma; Xili Yan; Taiwo Sesay; Haifeng Wang; Zhou Liang (Advances in Civil Engineering)
Aeolian sand is an important construction material in many desert regions. In order to study its engineering properties, samples were extracted from two sections within Yulin city, Shaanxi province of China. One set was collected from a site along the G210 highway that connects Yulin city and Inner Mongolia, and the other sampling site was along the provincial highway S204 that connects Yulin and Jingbian city. Sieve analyses using square mesh and round mesh sieves were conducted to determine the particle size distribution of the collected sand samples. In addition, scanning electron microscopy (SEM) and X-ray diffraction (XRD) were used to characterize the surface microstructure and mineral composition of the sand particles, respectively. Based on the sieve analyses results, the size distribution of the Aeolian sand particles in this region is mainly between 0.075 mm and 0.3 mm with low clay content (0.69–10.3%). Also, it was found that the square mesh is more effective than the round mesh for conducting sieve analysis of Aeolian sand, with the 0.15 mm sieve identified as the key sieve size. Using the percentage passing rates in the 0.15 mm square sieve as a classification index, the particle gradation of the sand particles was simplified into three classes: Class A (less than 30%), Class B (between 30% and 60%), and Class C (more than 60%). SEM observation revealed different profile configurations on the surfaces of the Aeolian sand particles including intensive pitting, corrosion marks, and cracks, while the XRD results indicated the presence of quartz and feldspar in more than 95% of the entire mineral composition of the sand particles. Minerals that are deleterious to cement and mortar used in road construction were present in negligible amounts. From the particle size characterization, it is possible to use Aeolian sand as a subgrade material in road construction due its lower clay content. Also, the negligible amount of minerals such as calcite and chlorite in the Aeolian sand mineral composition indicates its potential for use in cement and mortar without causing any complex chemical reactions. The findings of this study indicate the possibility of utilizing the Aeolian sand deposits in Yulin area as a road construction material and also provide a theoretical guide to encourage its widespread application in this regard.